Autoclave-Assisted Synthesis of Silver Nanoparticles using Metroxylon Sagu for Antibacterial Application - A., Jamaludin; C. K. M., Faizal (Informatics Publishing Limited, 2017)
Background/Objectives: Silver nanoparticles (AgNPs) have been conventionally synthesized through several complicated steps that require careful attention. In this study, a simplified green synthesis method for the production of AgNPs in one pot via autoclaving method was reported. Methods/ Statistical Analysis: Different concentrations of Sago solution were mixed with 1 mM AgNO3 and autoclaved at 121 °C for 20 min. The Sago acted as the reducing and capping agent as well as the stabilizer to produce the AgNPs. The synthesized AgNPS were characterized using UV-V is spectrometry, FTIR and EFTEM analysis. The antibacterial assay was also carried out using agar well diffusion method for the investigation of the antibacterial activity of the synthesized AgNPs against Gram positive (Micrococcus luteus) and Gram negative (Escherichia coli) bacteria. Findings: The UV-Vis spectrum for the synthesized AgNPs ranging between 410 – 415 nm, and the shifted peaks of the FTIR spectrum confirmed the presence of the synthesized AgNPs. From the EFTEM images, the AgNPs are spherical in shape and well distributed with average particle sizes of 17.2 ± 6.7 nm. The AgNPs also exhibited great antibacterial activities against both bacteria through the agar well diffusion as clearly observed in the inhibition zones. Application/Improvements: Autoclaved and sterilized AgNPs have been synthesized through an environment friendly way and has exhibited great antibacterial activities through the simple and fast method. These AgNPs are suitable for application as promising antibacterial agent in various applications especially in biomedical devices.